Impact of RING and BRCT Domain Mutations on BRCA1 Protein Stability, Localization, and Recruitment to DNA Damage - Nelson, Andrew C. (Radiat Res, 2010)
Mutations within the tumor suppressor BRCA1 cause the majority of hereditary breast and ovarian cancer cases. The BRCA1 protein is an important regulator of DNA double strand break repair and BRCA1 deficient cells are highly sensitive to ionizing radiation. Furthermore, BRCA1 function may contribute to G(2) cell cycle checkpoint enforcement. E3-ubiquitin ligase activity is the only known enzymatic activity of BRCA1, which is mediated by the N-terminal RING finger domain. The C-terminal BRCT repeat domain, which mediates protein-protein interactions, is the only other identified structural domain. By investigating cancer-linked mutations within each domain, we demonstrate that truncation of the BRCT domain greatly impairs the stability and nuclear localization of BRCA1 protein. A missense mutation within the RING domain does not affect these biochemical properties. However, both mutant forms of BRCA1 fail to co-localize in nuclear foci with the known BRCA1-interacting proteins BARD1 and BACH1, which are important for DNA repair. This failure occurs despite the continued ability of the RING mutant protein to interact with BACH1 and the ability of the BRCT mutant to interact with BARD1. Furthermore, neither mutant form of BRCA1 is recruited into DNA-damage-associated foci marked by γH2AX. Therefore, our data suggests that both the RING and BRCT domains of BRCA1 are required for an early step in the function of BRCA1 during DNA repair: recruitment to the sites of DNA damage.